Identitas Budaya dan Makna Simbolik pada Tradisi Penggunaan Kain Kuning Masyarakat Banjar - Salma, Ratu; Budhi, Setia (Huma: Jurnal Sosiologi, 2025)
Cultural symbols not only reside in artifacts but are also embedded in the beliefs and practices of society. The phenomenon of using yellow cloth in various traditional rituals, such as baayun maulid, betatamba, and pilgrimages to the graves of revered figures, reflects a collective belief in sacredness, protection, and spiritual connection with ancestors. This study aims to uncover the symbolic meaning of yellow cloth and explore its functions in the everyday life of the Banjar community, particularly within the context of local traditions and beliefs. This research employs a qualitative method with an ethnographic approach. Data were collected through observation, semi-structured interviews, and documentation. Seven key informants were selected using purposive sampling techniques. The findings reveal that the Banjar people perceive the yellow cloth as a sacred object, not merely for its aesthetic value, but for its rich symbolic meanings passed down across generations. However, a shift in meaning was found among younger generations, who tend to view the cloth more profanely and functionally. The perspective of symbolic interactionism is used to understand how the meaning of yellow cloth is constructed, maintained, and transformed through intergenerational social interaction. This study offers insights into the importance of preserving symbolic values in Banjar culture amid modern pressures and serves as a theoretical contribution to the study of local culture and symbolic sociology. Future research is encouraged to explore the dynamics of symbolic cultural transmission from generational and social media perspectives.